Central Arterial Stiffness Is Associated With Structural Brain Damage and Poorer Cognitive Performance: The ARIC Study. Issue 2 (22nd January 2019) - Palta, Priya; Sharrett, A. Richey; Wei, Jingkai; Meyer, Michelle L.; Kucharska‐Newton, Anna; Power, Melinda C.; Deal, Jennifer A.; Jack, Clifford R.; Knopman, David; Wright, Jacqueline; Griswold, Michael; Tanaka, Hirofumi; et al.
Abstract : Background: Central arterial stiffening and increased pulsatility, with consequent cerebral hypoperfusion, may result in structural brain damage and cognitive impairment. Methods and Results: We analyzed a cross‐sectional sample of ARIC‐NCS (Atherosclerosis Risk in Communities–Neurocognitive Study) participants (aged 67–90 years, 60% women) with measures of cognition (n=3703) and brain magnetic resonance imaging (n=1255). Central arterial hemodynamics were assessed as carotid‐femoral pulse wave velocity and pressure pulsatility (central pulse pressure). We derived factor scores for cognitive domains. Brain magnetic resonance imaging using 3‐Tesla scanners quantified lacunar infarcts; cerebral microbleeds; and volumes of white matter hyperintensities, total brain, and the Alzheimer disease signature region. We used logistic regression, adjusted for demographics, apolipoprotein E ɛ4, heart rate, mean arterial pressure, and select cardiovascular risk factors, to estimate the odds of lacunar infarcts or cerebral microbleeds. Linear regression, additionally adjusted for intracranial volume, estimated the difference in log‐transformed volumes of white matter hyperintensities, total brain, and the Alzheimer disease signature region. We estimated the mean difference in cognitive factor scores across quartiles of carotid‐femoral pulse wave velocity or central pulse pressure using linear regression. Compared with participants in the lowest carotid‐femoral pulse wave velocity quartile, participants in the highest quartile of carotid‐femoral pulse wave velocity had a greater burden of white matter hyperintensities ( P =0.007 for trend), smaller total brain volumes (−18.30 cm 3 ; 95% CI, −27.54 to −9.07 cm 3 ), and smaller Alzheimer disease signature region volumes (−1.48 cm 3 ; 95% CI, −2.27 to −0.68 cm 3 ). These participants also had lower scores in executive function/processing speed (β=−0.04 z score; 95% CI, −0.07 to −0.01 z score) and general cognition (β=−0.09 z score; 95% CI, −0.15 to −0.03 z score). Similar results were observed for central pulse pressure. Conclusions: Central arterial hemodynamics were associated with structural brain damage and poorer cognitive performance among older adults.